Heat transfers and micro-climatic effect of solar reflective coatings on buildings - Toh, Kui Ching (2014)
There has been an increasing demand to create new passive building cooling methods to tackle the global issues of urban heat island (UHI) effects which many developed nations are currently experiencing. Recent research has proven that coating a building with high solar reflective coatings is one of the feasible methods for passive cooling. In this study, the effectiveness of solar reflective coatings on the heat transfer into buildings and the micro-climatic effects it generate will be discussed based on in a tropical climate like Singapore. This study was conducted using building energy software named Integrated Virtual Environment (IES). Feasibility studies of using the software was validated by comparing the simulations results against the experimental results obtained from the test building in the industrial area of Nanyang Technological University. Simulation results were found to be within the upper and lower acceptable temperature limits after calibration which shows the feasibility of using IES in this experiment. The test building was modelled using IES and energy simulations were conducted based on the day with peak average solar radiation from the weather file of Singapore. Two separate cases were analysed, first being an uncoated roof surface with reflectivity of 0.3 while the other is a coated roof surface with solar reflective of 0.8. Computational Fluid Dynamic (CFD) simulations were also conducted to provide a visual study of the results. Simulations results showed that by increasing the reflectivity of a roof surface from 0.3 to 0.8, the surface temperatures of roof and ceiling can be reduced by up to 17.5oC and 1.2oC respectively in an air-conditioned room maintain at 25oC. In addition, the effects on the outdoor air temperature with the use of high solar reflectance coatings indicate a maximum reduction of 1.0oC, 0.7oC and 0.6oC for air temperature at a height of 0.5 m, 1 m and 1.5 m above the roof surface between a coated and uncoated roof surface. These results show the effectiveness of using solar reflective coatings in the reducing the heat transfer into building and its effectiveness in mitigating the impacts of urban heat island effects.